2012
DOI: 10.3390/ijms13021612
|View full text |Cite
|
Sign up to set email alerts
|

Tetrachloridocuprates(II)—Synthesis and Electron Paramagnetic Resonance (EPR) Spectroscopy

Abstract: Ionic liquids (ILs) on the basis of metal containing anions and/or cations are of interest for a variety of technical applications e.g., synthesis of particles, magnetic or thermochromic materials. We present the synthesis and the results of electron paramagnetic resonance (EPR) spectroscopic analyses of a series of some new potential ionic liquids based on tetrachloridocuprates(II), [CuCl4]2−, with different sterically demanding cations: hexadecyltrimethylammonium 1, tetradecyltrimethylammonium 2, tetrabutyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
11
1
Order By: Relevance
“…[Cu II 4 (L1) 2 (Cl) 4 , which is expected to be around 400 nm, is not observed [22][23][24]. This indicates that in solution the chlorides might dissociate to a situation where there is just Cu II Cl 2 present with and without coordinated L1.…”
Section: àcontrasting
confidence: 46%
“…[Cu II 4 (L1) 2 (Cl) 4 , which is expected to be around 400 nm, is not observed [22][23][24]. This indicates that in solution the chlorides might dissociate to a situation where there is just Cu II Cl 2 present with and without coordinated L1.…”
Section: àcontrasting
confidence: 46%
“…It is also known that the tetrahalido ion, [CoCl 4 ] 2− shows a magnetic moment of 4.56 BM which assumes the value of 4.47 BM for [Bmim] 2 [CoCl 4 ] [ 69 ]. These results show that there is no strong evidence of a metal-metal interaction, similar to data by Strauch et al [ 70 ] who observed very weak metal-metal interactions in similar compounds. Table 2 summarizes the thermal properties and magnetic moments of [Bmim] 2 [CuCl 4 ], [Bmim] 2 [CoCl 4 ] and [Bmim] 2 [MnCl 4 ].…”
Section: Resultssupporting
confidence: 91%
“…S9 †). [32][33][34] As mentioned before, an abrupt increase is observed in the absorption at 400 nm at the start of the reaction. This 'jump' is likely caused by a change in absorption spectrum when the chloride ions dissociate from the copper center.…”
Section: Dalton Transactions Papermentioning
confidence: 75%